Métodos de enseñanza aprendizaje para la lectoescritura con los educandos de tercer año elemental de la Unidad Educativa " Marco Aurelio Subía Martínez- Batalla de Panupali". - Vivanco Jorge, Verónica Claudia (2020)
This research addresses a problem about the insufficient development of literacy with students and educators in relation to the use of alternative methods during the teaching-learning process, therefore it is proposed as a general objective, to strengthen the teaching-learning process through the use of alternative methods for the development of literacy. The paradigm used is qualitative and as a basic applied modality because after observing and identifying different limitations in the educational process, it allows providing possible alternative solutions as well as building activities with alternative methods for the development of literacy, the type of research is explanatory because it allows us to discover organized methods with different processes and to promote the teaching of reading and writing with students who have difficulties, especially in the area of ​​language and literature, posing as a proposal; alternative methods in teaching practice for literacy in the classroom; which was validated by different users, thus contributing to the educational community.